2013
DOI: 10.1080/19371918.2011.592087
|View full text |Cite
|
Sign up to set email alerts
|

Daily Life or Diagnosis? Dual Perspectives on Perinatal Depression within Maternal and Child Health Home Visiting

Abstract: This study describes a qualitative inquiry–informing program development in a maternal and child home visiting program. Low-income women's perceptions of the meaning and experiences of depression were ascertained through focus groups and interviews. Simultaneously, the study examines staff member perceptions and roles related to depression. Specific findings from clients and staff reveal culturally situated beliefs about depression and stressful life events; comparing and contrasting these beliefs offers a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Our results confirmed that antenatal depression screening alone cannot achieve the same significant effects of preventing and reducing postpartum depression as our intervention did. Therefore, the importance of a tailored intervention after depression screening during pregnancy cannot be overemphasized (Price & Cohen-Filipic, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirmed that antenatal depression screening alone cannot achieve the same significant effects of preventing and reducing postpartum depression as our intervention did. Therefore, the importance of a tailored intervention after depression screening during pregnancy cannot be overemphasized (Price & Cohen-Filipic, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Australian Institute of Health and Welfare reports on the key causes of maternal death in Australia in 2008–2012 and notes that out of 16 psychosocial‐related deaths, 12 were suicide (AIHW, ). The susceptibility to psychosocial distress and mental health problems during the perinatal period is higher for women with vulnerabilities, in particular a history of mental health problems, substance use disorder, childhood abuse and domestic violence (Blegen, Hummelvoll, & Severinsson, ; Grant et al., ; Healey et al., ; Khan, ; Monzon et al., ; Muzik & Borovska, ; Price & Cohen‐Filipic, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, all data were self-reported by home visitors and thus present only a single perspective on very complex issues. Recent qualitative research suggests that HV clients' views of their own depressive symptoms and their preferred way of receiving help differs from their home visitors' perceptions (Price & Cohen-Filipic, 2013). Complementary surveys assessing client perspectives as well as perspectives of treatment providers, program supervisors and administrators, and other stakeholders would provide a more complete picture, particularly of the potential barriers to home visitor management of client behavioral health risks and client access to needed services.…”
Section: Limitationsmentioning
confidence: 99%